A peroxisomal thioesterase plays auxiliary roles in plant β‐oxidative benzoic acid metabolism. (6th February 2018) - Adebesin, Funmilayo; Widhalm, Joshua R.; Lynch, Joseph H.; McCoy, Rachel M.; Dudareva, Natalia
Summary: Peroxisomal β‐oxidative degradation of compounds is a common metabolic process in eukaryotes. Reported benzoyl‐coenzyme A (BA‐CoA) thioesterase activity in peroxisomes from petunia flowers suggests that, like mammals and fungi, plants contain auxiliary enzymes mediating β‐oxidation. Here we report the identification of Petunia hybrida thioesterase 1 (PhTE1), which catalyzes the hydrolysis of aromatic acyl‐CoAs to their corresponding acids in peroxisomes. PhTE1 expression is spatially, developmentally and temporally regulated and exhibits a similar pattern to known benzenoid metabolic genes. PhTE1 activity is inhibited by free coenzyme A (CoA), indicating that PhTE1 is regulated by the peroxisomal CoA pool. PhTE1 downregulation in petunia flowers led to accumulation of BA‐CoA with increased production of benzylbenzoate and phenylethylbenzoate, two compounds which rely on the presence of BA‐CoA precursor in the cytoplasm, suggesting that acyl‐CoAs can be exported from peroxisomes. Furthermore, PhTE1 downregulation resulted in increased pools of cytoplasmic phenylpropanoid pathway intermediates, volatile phenylpropenes, lignin and anthocyanins. These results indicate that PhTE1 influences (i) intraperoxisomal acyl‐CoA/CoA levels needed to carry out β‐oxidation, (ii) efflux of β‐oxidative products, acyl‐CoAs and free acids, from peroxisomes, and (iii) flux distribution within the benzenoid/phenylpropanoid metabolic network. Thus, this demonstrates that plant thioesterases play multiple auxiliary roles in peroxisomal β‐oxidative metabolism. Significance Statement: We discovered that, like mammals and fungi, plants also contain peroxisomal acyl‐coenzyme A (CoA) thioesterases that play auxiliary roles in modulating β‐oxidative metabolism. Using the petunia β‐oxidative pathway for benzoic acid biosynthesis as an exploratory tool, we have shown that the isolated peroxisomal aromatic acyl‐CoA thioesterase influences (i) intraperoxisomal acyl‐CoA/CoA‐SH levels needed to carry out β‐oxidation, (ii) efflux of β‐oxidative acyl‐CoA and free‐acid products from peroxisomes, and (iii) flux distribution between benzenoid and phenylpropanoid metabolic pathways.